2022
DOI: 10.1039/d1ra09244h
|View full text |Cite
|
Sign up to set email alerts
|

Droplet motion on a wrinkled PDMS surface with a gradient structural length scale shorter than the droplet diameter

Abstract: Gradient wrinkled PDMS surfaces were fabricated through metal film deposition with installation of a mask and the motion of impinged droplets on the surfaces followed the structural gradient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…After cooling, the surface of PDMS—now with deposited metal on it—returns to its initial state, and wrinkles are formed. The result is coherent with the state of the art [ 20 , 21 , 22 , 23 , 24 , 25 ]. Therefore, the PDMS/metal wrinkles, shown in Figure 2 c,d, result from the plasma treatment which occurs in the course of sputtering.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…After cooling, the surface of PDMS—now with deposited metal on it—returns to its initial state, and wrinkles are formed. The result is coherent with the state of the art [ 20 , 21 , 22 , 23 , 24 , 25 ]. Therefore, the PDMS/metal wrinkles, shown in Figure 2 c,d, result from the plasma treatment which occurs in the course of sputtering.…”
Section: Resultssupporting
confidence: 85%
“…The authors also fabricated tailored wrinkles based on Cu and thin PDMS [ 21 ]. Promising applications for tailored wrinkled soft metalized layers [ 22 , 23 ] include strain sensors [ 24 ] and droplet motion devices [ 25 ]. However, considering the published works, there is no clear and univocal understanding of the wrinkle formation mechanism and behavior of large-area freestanding metallized soft polymer layers.…”
Section: Introductionmentioning
confidence: 99%
“…26 Recent work has shown that the motion of droplets on a solid surface is significantly affected by the morphology of the surface. 27 Liu et al 28 demonstrated that mechanical measurement methods can be used to characterize the wettability of solid surfaces; such measurement techniques also represent an effective method to quantify the lateral friction force at the solid-liquid interface. Mannetje et al 29 used a simple force sensor based on capillary optical imaging to characterize the hysteresis motion of the drop along the surface.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Creating wettability gradients on soft surfaces especially on polydimethylsiloxane (PDMS) is of great interest due to the potential applications in microfluidics, self-cleaning surfaces, smart devices, etc. 1,[19][20][21][22][23] Wettability gradients induced by chemical gradients have been prepared by the surface modifications of soft surfaces through various chemical treatments like plasma treatment, the immersion technique, electrochemical methods, etc. [24][25][26] Wettability gradients from morphological gradients can be prepared by controlled variation of the surface roughness, shape, size, etc.…”
Section: Introductionmentioning
confidence: 99%